Bacterial community structure in banana rhizosphere of Orang Asli fields and commercial plantations, as revealed by 16S rRNA gene sequences / Jason Lee Yee Neng - Jason Lee , Yee Neng (2018)
Bacteria play important roles in the soil ecosystem, and in the rhizosphere, their dynamic and complex nature could be either beneficial or deterimental to the plants. Banana grows well in the tropics and is popularly grown in Orang Asli (OA) (indigenous people) settlements. Bananas are also grown in commercial plantations. In traditional planting practices, the OA do not add pesticide nor fertiliser to their crops which are planted for self-sustenance mainly. On the other hand, fertiliser and pesticide are added to commercial banana plantations as a means to maximise yield. Rhizosphere soils were collected from several varieties of banana plants: “Pisang Siam”, “Pisang Nangka” and “Pisang Nipah” in one OA field (Paya Mendoi, Pahang); and “Pisang Berangan” and “Pisang Nipah” in one commercial plantation (Parit Serong, Selangor). Rhizosphere from only “Pisang Nipah” was collected from another OA field (Kampung Pian, Pahang) and another commercial plantation (Mersing, Johor). The rhizosphere bacteria were analysed by clone library construction of the 16S rRNA gene. From the result of the clone libaries, Acidobacteria, Proteobacteria and Actinobacteria were found in all the soil. Within the OA fields, Acidobacteria was dominant in the rhizosphere of all of the 3 banana varieties in Paya Mendoi but not in Kampong Pian where there was more Proteobacteria. Conversely, Bacteroidetes (13.79%) and Cyanobacteria (0.86%) were found in Kampong Pian but little to none found in Paya Mendoi. Comparing the commercial plantations, the Nitrospirae (9.4% in Pisang Nipah; 0.6% in Pisang Berangan) and Gemmatimonadetes (1.3% in Pisang Nipah; 0.9% in Pisang Berangan) were found in Parit Serong but none in Mersing. The overall bacterial communities in banana rhizosphere of OA fields and commercial plantations showed little differences between them where certain minor bacteria phyla such as Nitrospirae, Bacteroidetes, Chloroflexi, Verrumicrobia, Gemmatimonadetes, Cyanobacteria and uncultured bacteria were variable (found in some soil but not all). The commercial plantation in Parit Serong had higher nitrogen (N), phosphorus (P) and potassium (K) content compared to the OA banana fields, meanwhile, the N, P, K contents in the commercial plantation in Mersing were roughly similar to the OA fields, but calcium and sodium contents were higher in both the commercial plantations than the OA fields. No organochlorine and organophosphorus (common constituents of pesticides) was detected in the rhizosphere of both the OA fields and the commercial plantations. One possible reason is the chemicals could have degraded or washed off by the time the rhizosphere samples were collected. To sum up, the bacterial communities were roughly similar between banana varieties but different when comparing between the two OA fields and between the two commercial plantations. The rhizosphere within the same location showed a similar bacteria composition but different when compared between different locations. Meanwhile, the PAST analysis (Diversity Analysis Using Paleontological Statistics) supported the evidence of higher bacterial diversity in OA banana fields compared to the commercial plantations.